Association of estimated plasma volume and weight loss after long‐term administration and subsequent discontinuation of the sodium‐glucose cotransporter‐2 inhibitor tofogliflozin. Issue 7 (4th May 2021) - Matsubayashi, Yasuhiro; Yoshida, Akihiro; Suganami, Hideki; Oe, Momoko; Sato, Takaaki; Yaguchi, Yuta; Fujihara, Kazuya; Yamada, Takaho; Tanaka, Shiro; Kaku, Kohei; Sone, Hirohito
Abstract: Sodium‐glucose cotransporter‐2 inhibitors (SGLT2) are drugs that have been reported to have several effects through the regulation of plasma volume, for example, antihypertensive effects. This study aimed to clarify the impact of long‐term administration and subsequent discontinuation of the SGLT2 inhibitor tofogliflozin on estimated plasma volume (ePV), brain natriuretic peptide (BNP) and the relationship between changes in ePV, BNP and body weight (BW). Data from 157 participants with type 2 diabetes receiving tofogliflozin monotherapy in a phase 3 study were analysed. Changes in variables or correlations among them during a 52‐week administration and a 2‐week post‐treatment period were investigated. Percent change in ePV was calculated using the Strauss formula. Significant decreases in BW, ePV and ln‐transformed BNP (ln‐BNP) were noted by week 52. %ΔBW was not significantly correlated with %ΔePV and Δln‐BNP, while %ΔePV was significantly correlated with Δln‐BNP. Two weeks after discontinuation of tofogliflozin, BW, ePV and ln‐BNP were significantly increased. %ΔBW was significantly correlated with %ΔePV and Δln‐BNP. Furthermore, ePV and BNP were significantly higher than baseline levels.